2015
DOI: 10.1021/jacs.5b05735
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dual 1,1-H-Abstraction/Insertion for Domino Spirocyclizations

Abstract: A catalytic domino spirocyclization of 1,7-enynes with simple cycloalkanes and cyclo-1,3-dicarbonyls has been established via multiple C-C bond formations from alkynyl/alkenyl functions and dual α,α-C(sp(3))-H abstraction/insertion. The reaction involves addition, 6-exo-dig cyclization and radical coupling sequences under convenient catalytic conditions and provides a concise access to spiro cyclopenta[c]quinolines in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(56 citation statements)
references
References 75 publications
1
53
0
1
Order By: Relevance
“…On the basis of a literature survey, [14] our previous report [15] and controlled experimental outcomes, a tentative mechanism for the formation of products 3 is outlined in Scheme 5. tert-Butoxy radical generated in situ from the Fe(II)-assisted homolysis of DTBP abstracts a hydrogen atom from the cycloalkane to form a cycloalkyl radical. Then, the intermolecular addition of the in-situ-generated cycloalkyl radical to oxygen-tethered 1,7-conjugated enynes 1 delivers radical intermediates A, followed by intramolecular 6-exo-dig cyclization and H-abstraction to afford intermediates C. The 5-endo-trig cyclization of C gives intermediates D, which undergo oxidation and deprotonation to yield spiro products 3.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of a literature survey, [14] our previous report [15] and controlled experimental outcomes, a tentative mechanism for the formation of products 3 is outlined in Scheme 5. tert-Butoxy radical generated in situ from the Fe(II)-assisted homolysis of DTBP abstracts a hydrogen atom from the cycloalkane to form a cycloalkyl radical. Then, the intermolecular addition of the in-situ-generated cycloalkyl radical to oxygen-tethered 1,7-conjugated enynes 1 delivers radical intermediates A, followed by intramolecular 6-exo-dig cyclization and H-abstraction to afford intermediates C. The 5-endo-trig cyclization of C gives intermediates D, which undergo oxidation and deprotonation to yield spiro products 3.…”
Section: Figurementioning
confidence: 99%
“…[12] For these reasons, considerable efforts have been devoted to the use of 1,7-enynes for assembling highly complex structures of chemical and biomedical importance. [15] Scheme 1 Synthesis of polycyclic chromen-2-ones Inspired by these interesting studies and considering the significance of cyclopenta[c]chromen-2-ones, we decided to employ oxygen-tethered 1,7-enynes as a radical acceptor to capture cycloalkane-derived C-center radicals, thereby evaluating the feasibility of the formation of cyclopenta[c]chromen-2-ones through catalytic C(sp 3 )-H bifunctionalization. During these processes, N-linked 1,7-enynes were carefully explored to access spiro-substituted cyclopenta[c]quinolin-4-ones while only two examples of cyclopenta[c]chromenes were obtained using oxygen-linked 1,7-enynes (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In these transformations, regioselective radical addition cascades were postulated involving the participation of a vinyl intermediate, followed by hydrogen abstraction and radical coupling to give spiro-substituted cyclopenta[ c ]quinolones (Scheme 1d). 14 We reasoned that under suitable oxidative conditions, the sulfonyl radicals could be engaged in additional bond-forming events with N -tethered 1,7-enynes 1 to form the vinyl intermediates, which would be trapped by adequate radicals partners through radical coupling, thus expanding the synthetic utility of these processes. Herein we report the successful realization of this concepts via a novel cascade 1,7-enyne-cyclization trapped by two different radicals, which enabled the one-pot synthesis of densely functionalized 3,4-dihydroquinolin-2(1 H )-ones with unprecedented substitution patterns through halosulfonylation of 1,7-enynes (Scheme 1e).…”
mentioning
confidence: 99%
“…It has been reported that 1,3‐dicarbonyl compounds could be applied as alkyl radical precursors under the oxidative conditions, which further added to C=C bond furnish C–C bond formation products . In 2018, our group reported a convenient radical cascade cyclization of 2‐(allyloxy)arylaldehydes 47 with 1,3‐dicarbonyl compounds 48 to synthesize 1,5‐/1,3‐dicarbonyl‐containing chroman‐4‐ones 49 in the presence of AgNO 3 /K 2 S 2 O 8 under mild reaction conditions (Scheme ) .…”
Section: Radical Strategies For the Synthesis Of 3‐substituted Chrmentioning
confidence: 99%